Economic Burden of COVID-19: A Systematic Review - Richards F; Kodjamanova P; Chen X; Li N; Atanasov P; Bennetts L; Patterson BJ; Yektashenas B; Mesa-Frias M; Tronczynski K; Buyukkaramikli N; El Khoury AC (Dove Medical Press, 2022)
Fayolah Richards,1 Petya Kodjamanova,2 Xue Chen,3 Nicole Li,4 Petar Atanasov,5 Liga Bennetts,6 Brandon J Patterson,1 Behin Yektashenas,1 Marco Mesa-Frias,7 Krzysztof Tronczynski,8 Nasuh Buyukkaramikli,9 Antoine C El Khoury1 1Janssen Global Services, Raritan, NJ, USA; 2HEMA Amaris, Sofia, Bulgaria; 3HEMA Amaris, Shanghai, People's Republic of China; 4HEMA Amaris, Toronto, Canada; 5HEMA Amaris, Barcelona, Spain; 6HEMA Amaris, Montréal, Canada; 7Janssen Scientific Affairs LLC, Titusville, NJ, USA; 8EMEA Janssen, Warsaw, Poland; 9R&D Janssen, Beerse, BelgiumCorrespondence: Fayolah Richards, Email frichar4@its.jnj.comObjective: To review and qualitatively synthesize the evidence related to the economic burden of COVID-19, including healthcare resource utilization and costs.Methods: A systematic review of studies that assessed the economic burden [eg, direct costs, productivity, macroeconomic impact due to non-pharmaceutical interventions (NPIs) and equity] of COVID-19 was conducted by searches in EMBASE, MEDLINE, MEDLINE-IN-PROCESS, and The Cochrane Library, as well as manual searches of unpublished research for the period between January 2020 to February 2021. Single reviewer data extraction was confirmed independently by a second reviewer.Results: The screening process resulted in a total of 27 studies: 25 individual publications, and 2 systematic literature reviews, of narrower scopes, that fulfilled the inclusion criteria. The patients diagnosed with more severe COVID-19 were associated with higher costs. The main drivers for higher costs were consistent across countries and included ICU admission, in-hospital resource use such as mechanical ventilation, which lead to increase costs of $2082.65 ± 345.04 to $2990.76 ± 545.98. The most frequently reported indirect costs were due to productivity losses. On average, older COVID-19 patients incurred higher costs when compared to younger age groups. An estimation of a 20% COVID-19 infection rate based on a Monte Carlo simulation in the United States led to a total direct medical cost of $163.4 billion over the course of the pandemic.Conclusion: The COVID-19 pandemic has generated a considerable economic burden on patients and the general population. Preventative measures such as NPIs only have partial success in lowering the economic costs of the pandemic. Implementing additional preventative measures such as large-scale vaccination is vital in reducing direct and indirect medical costs, decreased productivity, and GDP losses.Keywords: covid-19, economic Impact, symptom Burden, health Economics, vaccines, costs